2019
DOI: 10.1002/ijc.32735
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic acid is a drug with the potential to be repurposed for suppressing tumor growth and metastasis in osteosarcoma treatment

Abstract: Our previous review of proteomics data showed that in osteosarcoma, some overexpressed proteins were targets of FDAapproved immunosuppressive and anti-arrhythmic drugs, including mycophenolate mofetil (MMF), ribavirin, leflunomide, azathioprine and digoxin. Here, these drugs were screened for growth inhibitory effects in human osteosarcoma cell lines, including MNNG/HOS, U2OS, SaOS-2, MG-63 and 143B cells. Only mycophenolic acid (MPA), an active metabolite of MMF, efficiently inhibited osteosarcoma cell growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…We next investigated whether transient NK cell depletion increased the efficiency with which intravenous inoculation of 143B human osteosarcoma cells produced lung metastases. As mentioned earlier, previous research established that these cells could form lung metastases after intravenous injection, [5][6][7][8][9] but 1-2 million cells were injected in those studies, implying that seeding to the lungs was very inefficient. As with the KRIB cells, tail vein injections of 150,000 luciferase-tagged 143B cells failed to yield lung metastases (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated whether transient NK cell depletion increased the efficiency with which intravenous inoculation of 143B human osteosarcoma cells produced lung metastases. As mentioned earlier, previous research established that these cells could form lung metastases after intravenous injection, [5][6][7][8][9] but 1-2 million cells were injected in those studies, implying that seeding to the lungs was very inefficient. As with the KRIB cells, tail vein injections of 150,000 luciferase-tagged 143B cells failed to yield lung metastases (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, only one human osteosarcoma cell line, 143B, has been used by multiple groups to induce so-called ''experimental metastasis.'' [5][6][7][8][9] Those studies involved injection of at least one million cells to achieve lung metastases. The dearth of examples of osteosarcoma cell lines published to form metastases after intravenous injection, coupled with the large number of 143B cells required to achieve this, implies that the process by which human osteosarcoma cells move from the blood to the lungs in nude mice is extremely inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The initial dose of mycophenolate mofetil at 5 g/day which is planned to be used in this phase II clinical trial is based on the pharmacologically active dose in mice, from which human equivalent dose is then calculated, as well as clinically experienced doses in humans. Tumor growth inhibition was evident in mice treated with mycophenolate mofetil at 200 mg/kg/day [18], so mycophenolate mofetil at the dose of 1 g/day or more is expected to be pharmacologically active in humans. In clinical practice, longterm treatment with mycophenolate mofetil at the dose of 2 to 3 g/day has a satisfactory safety profile in organ transplant recipients [47,48].…”
Section: Rationale For the Experimental Dose Of Mycophenolate Mofetilmentioning
confidence: 99%
“…In 2010, Fellenberg et al reported the observed overexpression of IMPDH in metastatic and chemo-resistant osteosarcoma cell lines, and pharmacological inhibition of IMPDH could result in a reduction of cell viability and cell proliferation [17]. A recent in vitro study has revealed the anticancer activity of MPA against osteosarcoma cell lines, with the half maximal inhibitory concentration (IC 50 ) of 0.46-7.30 μM across all tested cell lines [18]. The in vivo experiment has shown the inhibition of tumor growth and lung metastasis of osteosarcoma in mice treated with mycophenolate mofetil [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation